Factors Affecting Bank Risk-Taking: Evidence from Southeast Asian Countries - Tran, Hung Son (University of Economics Ho Chi Minh City, 2023)
In this paper we use a dynamic panel data model (system GMM estimator) to analyze bank-specific and macroeconomic determinants of bank risk as measured by the Z-score of 70 listed commercial banks operating in six Southeast Asian countries over the period from 2005 to 2013. Our results indicate that asset structure, capitalization, size, and the stock market development are negatively and significantly related to bank risk, which is, in turn, positively related to efficiency, revenue diversification, and the banking system development.